Digital Photography Just the Steps for Dummies (Wiley Publishing, 2011)
Digital photography is sweeping the country, and it’s easy to see why. You can take pictures of anything, do it quickly, see instantly what you got (or didn’t get), save only the stuff you like, and share your pictures as prints, on the Web, as a slideshow, or even on things like mugs and mousepads. A digital camera and the appropriate software let you